AfterWards: A Narrative Medicine Program at Johns Hopkins Medicine and in China - Lauren Small (Wolters Kluwer Health/LWW, 2023)
Narrative medicine is a multidisciplinary field of inquiry and practice based on the premise that medical care takes place in the context of stories. Research on narrative medicine training suggests that it conveys benefits such as improved communication skills and personal and professional growth to physicians, medical students, and other health care providers. Narrative medicine can promote empathy and trust between patients and physicians and foster self-care. In 2014, the author and a colleague started an ongoing inter-disciplinary narrative medicine program in the Children's Center of the Johns Hopkins Hospital called AfterWards. The program, which meets monthly, is open to all on a volunteer basis. Through literature, art, and writing, AfterWards nurtures empathy, encourages reflective practice, and builds community among a diverse group of health care providers. Through a series of lectures and workshops at Johns Hopkins Medicine, Peking Union Medical College, and Fudan Hospital in Shanghai, the author has introduced AfterWards to Chinese medical educators and clinicians. Working with Dr. Marta Hanson, she created an AfterWards Facilitator's Guide for the use of Chinese practitioners. A recent White Paper on Chinese health care indicates that an infusion of humanities-based education, of which narrative medicine forms a part, can help rebuild patient-physician trust. Recently, there has been an increase in interest in narrative medicine in the United States and China. However, more research is needed to demonstrate the impact of programs like AfterWards. Challenges to the implementation of narrative medicine programs remain, most significantly in terms of expertise, resources, and time.